Learning Theory and Adult Education - Knud Illeris (Adult Education Research Conference, 2000)
Today a majority of the participants in adult education are unskilled or unemployed adults who must combine acquiring a professional qualification with a change of identity and way of life. As a foundation of such education, staff and planners need a comprehensive learning theory that includes the cognitive, psychodynamic and social-societal dimensions of learning.